Dynamic capabilities in the process of building the effectiveness of the business model of retail fuel sales market - Rajewska, Katarzyna (Dynamiczne zdolności w procesie budowania efektywności modeli biznesu na rynku detalicznej sprzedaży paliw, 2019)
The aim of the article is to promote research on the concept of dynamic capabilities in the process of building the efficiency of the business model of enterprises on the fuel sales market. The starting point of the article is the presentation of the retail fuel sales market in Poland and possible change scenarios. The dynamic development of the sector has made fuel stations an important element of public infrastructure. However, due to the high level of competitiveness, the entities manage differently with survival and their development. The concept of dynamic capabilities, which is one of the most promising approaches to explaining differences in financial results, seems to be interesting. The article shows some of the results of the research procedure conducted among participants of the fuel sales market in relation to the environment of the organization, business model and dynamic capabilities in terms of both process and resources
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 3, s. 16-23
Keywords: retail fuel sales market; dynamic capabilities; effectiveness; business models; rynek detaliczny; sprzedaż paliw; efektywność; modele biznesu